First report of an outbreak of cerebral coenurosis in Dhofari goats in Oman - Mahmoud Shaban El-Neweshy; Reda Elbastawisy Khalafalla; Mohamed Mohamed Sayed Ahmed; Julanda Hamad Al Mawly; El-Sayed Mohamed El-Manakhly (Revista Brasileira de Parasitologia Veterinária)
Abstract This study documented the first outbreak of cerebral coenurosis in goats in Salalah, southern Oman. Deaths of 130 (16.6%) adult native goats in a herd (n=780) were reported from January to June 2017. Affected goats showed various nervous signs ended by death. Investigations for thiamine deficiency, polioencephalomalacia, caprine arthritis encephalitis, and listeriosis were negative. Upon necropsy, multiple (1-4) thin-walled cysts 2-3.5 cm in diameter containing clear fluid with numerous clusters of protoscolices in the cerebrum and cerebellum had replaced the brain parenchyma, causing space-occupying lesions. Parasitologically, the recovered cysts were Coenurus cerebralis, based on the arrangement of protoscolices, and the number and size of their hooks. Morphologically, each protoscolex had four suckers and a rostellum with double-crown hooks. The large and small hooks were 157.7±0.5 µm and 115±0.6 µm in length, respectively. Histopathologically, the parasite destroyed the affected tissues associated with multifocal to diffuse lymphocytic, non-suppurative meningoencephalitis; ischemic neuronal necrosis; and malacia. This is the first report of cerebral coenurosis in livestock in Oman, which should alert the local public health authorities for the application of prevention and control measures.